Structural and Thermal Performance Assessment of Shipping Container as Post-Disaster Housing in Tropical Climates - Zafra, Richelle G.; Mayo, John Rheynor M.; Villareal, Patrick Jasper M.; De Padua, Victor Mikael N.; Castillo, Ma. Hazel T.; Sundo, Marloe B.; Madlangbayan, Marish S. (Salehan Institute of Higher Education, 2021)
Shipping Containers (SC) are a viable option as temporary or permanent housing for disaster victims due to their modularity, strength, and availability in large quantities around the world. While SCs as alternative housing has been extensively explored, few studies have focused on the structural and thermal performance of SCs in a tropical monsoon climate. This paper aims to contribute to a better knowledge of SC building construction by (1) investigating the SCs structural performance when subjected to a variety of loads, including gravity, earthquake, and very strong typhoon, and (2) assessing the thermal performance in a hot and humid climate. The case of Leyte, Philippines, a hot, humid, and typhoon-frequented region, is considered in this study. To meet the objectives, two SCs were combined to build a single-family house. First, the structural strength of the SCs, including the effect of cuts and openings, were investigated using finite element analysis. Second, the thermal condition of the SC was compared using four models with different insulation materials: no insulation, PE foam insulation (R-12), slightly higher insulation (R-13 fiberglass batt), and very high insulation (R-49 fiberglass batt) through building energy simulation. The paper concludes that SCs have inherently high strength and can withstand strong wind and earthquake. Stresses due to cuts and openings were minimized when the cuts/openings were placed far from the corner posts. On the other hand, increasing insulation R-value did not improve the indoor thermal condition of the SCs. More work needs to be done on making SCs thermally comfortable in hot and humid climates.Â Doi: 10.28991/cej-2021-03091735 Full Text: PDF